Cell Intrinsic Roles of Apoptosis-Associated Speck-Like Protein in Regulating Innate and Adaptive Immune Responses - Hoda Hassan; Amal O. Amer (The Scientific World Journal, 2011)
The role of apoptosis-associated speck-Like protein (ASC) in the assembly of the inflammasome complex within macrophages has been elucidated in several studies. In this particular role, ASC functions as an adaptor protein by linking nod-like receptors (NLRs) and procaspase-1, thereby leading to the activation of caspase-1 to cleave inflammatory cytokines IL-1β and IL-18 and inducing pyroptosis. It has been noted that ASC maintains inflammasome-independent roles, including but not limited to controlling the expression of Dock2 and mitogen-activated protein kinases (MAPK/ERK2) and regulating the NF-κB pathway. This paper will emphasize the major roles of ASC during pathogen infection, the mechanisms by which it mediates inflammation, and discuss its more recently discovered functions.